If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -1)(2x + 9) = 0 Reorder the terms: (-1 + 9x)(2x + 9) = 0 Reorder the terms: (-1 + 9x)(9 + 2x) = 0 Multiply (-1 + 9x) * (9 + 2x) (-1(9 + 2x) + 9x * (9 + 2x)) = 0 ((9 * -1 + 2x * -1) + 9x * (9 + 2x)) = 0 ((-9 + -2x) + 9x * (9 + 2x)) = 0 (-9 + -2x + (9 * 9x + 2x * 9x)) = 0 (-9 + -2x + (81x + 18x2)) = 0 Combine like terms: -2x + 81x = 79x (-9 + 79x + 18x2) = 0 Solving -9 + 79x + 18x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -2x)(1 + -9x) = 0Subproblem 1
Set the factor '(-9 + -2x)' equal to zero and attempt to solve: Simplifying -9 + -2x = 0 Solving -9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 0 + 9 -2x = 0 + 9 Combine like terms: 0 + 9 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5Subproblem 2
Set the factor '(1 + -9x)' equal to zero and attempt to solve: Simplifying 1 + -9x = 0 Solving 1 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -9x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 0 + -1 -9x = 0 + -1 Combine like terms: 0 + -1 = -1 -9x = -1 Divide each side by '-9'. x = 0.1111111111 Simplifying x = 0.1111111111Solution
x = {-4.5, 0.1111111111}
| 3x+1=6x+10 | | -26+5n=-5n-6(1-n) | | S-2s+3s-4s+5s=s+100 | | 9x+5(4+8x)= | | 2r^2+15r-19=0 | | 12+x=1 | | 4(2x+3)+3x=45 | | 6r+2=r+12 | | 8x+20-2x=40 | | 8q+8q= | | 4x-2y=6 | | 7(y+3)=98 | | 3a-13=19 | | Y-7=10 | | x+2x+3x+4x=10+20+30+40 | | 8p+p= | | 5=5(x-5)+2-4x | | 3(x+4)+6x=66 | | 6y+6+8y-6= | | 6x+5=-(x-33) | | 11r-5r+6r=168 | | 4x+10=2x+14 | | 8x+30=8x+3 | | 3+5j+4= | | 25=3(5-2y)+5 | | 4x+34=14x-76 | | x^2+2x=80 | | 7x+y=-33 | | 3x^2-18x+24=0 | | -6(-2+3g)= | | 11x-15=8x+3 | | 3(2x+1)+5=25 |